Provide a decision support system for locating new businesses (Ccase study: Locating toy manufacturing) - Amirhossein Rahbar; Ali Lahoutian; Mahmoud Vahedi Moghaddam (Journal of Information Technology Management)
Concept of locating business units includes the most important factors in their success and one the most competitive advantage of industrial units. Entrepreneurs have been considered in this context, and different mathematical models have been developed. This paper aims to develop a decision support system based on a mathematical model in linear programming. In a comprehensive approach to this article, three general headings can be recognized. First, as background concepts related to decision support systems, expert systems and mathematics of location reviewed. On the second part, the foundations of mathematics and logic model used in this study is explained. Finally, the samples software designed to implement the model are introduced and as a case study finding a best place for a toy manufacturing is studied and based on the outputs of software the province of Qom have introduced.